Development of a power meter for a bicycle - Liew, Keat Ken (2018)
Bicycle power meters are used to measure cyclist’s power output as he pedals to convert potential energy into kinetic energy to propel forward. Originally developed for professional cyclists, it has been gaining popularity among road cyclists of all levels. However, power meters available today are marketed with a degree of accuracy (usually ±2%) that varies between manufacturers and comes at a high price tag as well. As a continuation of project done by previous student, this project focuses on developing a power meter with a full-bridge connection circuit which could compete with the market standard of accuracy by designing and completing the circuitry entirely in the laboratories of Nanyang Technological University. Static tests will also be conducted to determine the accuracy of the power meter.